Group Counseling Management Based On Cognitive Behavior Therapy For Mental Retarded Students (A Site Study at SMPLB Bina Putera Ambarawa, Semarang) - Sulistyowati, Sulistyowati (2012)
Focus of this study is on the characteristics of group counseling based on cognitive behavior therapy at SMPLB (Special Secondary School) Bina Putera Ambarawa, Semarang. This study has three objectives. The first is describing the characteristic of organizational structure of group counseling based on cognitive behavior therapy. Secondly, it is describing the characteristic of mental retarded students. And finally, the research aims at classifying the characteristic of group counseling based on cognitive behavior therapy for mental retarded students. It is a qualitative research using ethnography design. This research was done at SMPLB Bina Putera Ambarawa, Semarang. The main subject included the principal, counselor and classroom teacher. Data collection method used in-depth interview, observation, and documentation. Data analysis technique of this research used an analysis arranged in site. the component of analyzing data includes data collection, data reduction, data display and conclusion. Data Validity used a triangulation method. This finding suggests that (1) the organizational structure of group counseling based on cognitive behavior therapy at SMPLB Bina Putera Ambarawa is compiled by including the role and task of each parties. The principal has a role as the supervisor, the classroom teacher as the executor of the program of group counseling based on cognitive behavior therapy. (2) The mental retarded students at SMPLB Bina Putera Ambarawa are different with the other normal students. Their physical condition, especially the head size. Their behavior also needs an adjustment to communicate. But with the group counseling based on cognitive behavior therapy, the mental retarded students can do several activities like the other normal students although it is far from perfect. (3) Group counseling based on cognitive behavior therapy for mental retarded students is held by giving students to tell their problem experienced. Students learn to dare to express their opinion in front of their friends. There are four stages in the group counseling based on cognitive behavior therapy for the mental retarded students such as formation, transition, action, and finishing stage. Evaluation is done by observing students' behavior which is done by the classroom teacher, counselor, and subject teacher.